KAPASITAS OTORITAS JASA KEUANGAN (OJK) DALAM PERLINDUNGAN PRODUK INVESTASI TABUNGAN EMAS DI PT. PEGADAIAN SYARIAH DAN KONVENSIONAL: THE CAPACITY OF THE FINANCIAL SERVICES AUTHORITY (OJK) IN PROTECTION OF GOLD SAVING INVESTMENT PRODUCTS IN PT. SHARIA POWDERSHIP AND ACCORDING TO CONVENTIONAL LAW NO. 21 YEAR 2011 - andhika naufal; Apik Hadiarlamsyah; Lutfizar S (Fakultas Syariah IAIN Kediri, 2022)
The government appoints the Financial Services Authority to supervise, foster and provide regulations regarding the Capital Market with the regulations in Law Number 21 of 2011 concerning the Financial Services Authority. In this study, the capital market in question is in the form of a limited liability company, namely PT. Pegadaian (Persero). The form of this company's financial services is a pawnshop. The other development in this company is in the form of gold investment. The company's goal is to provide convenience, especially for the lower middle class, to invest in gold by opening a gold savings account. The existence of this program has made other companies file lawsuits related to gold savings investment products. With the protection from OJK providing as a witness and providing an operational license number S-427/NB.11/2016 dated 17/02/2016 regarding the Gold Savings Pegadaian investment product, this program was inaugurated by the government and OJK given by PT. Pawnshop as the manager. The update related to the gold savings investment program was resubmitted and approved by the OJK with a new licensing letter number S-476/NB.111/2019 on 09/11/2019 regarding the approval of PT. Gold Savings Investment Products. Pegadain (Persero). So, PT. Pegadaian obtained a complete patent on the operational license for the gold savings investment product, although there are other companies with the same name as PT. pawnshop. Moreover, the implementation system in PT. Pawnshops differ by other companies that are suing. Keywords: OJK Regulation Law Number 21 of 2011, PT. Pegadaian, Gold Saving Investment Product